The Use of Audio Lingual Method to Improve the students’ Speaking Ability at SMA Anugerah Harapan Bangsa Medan - Saragih, Marice; Panggabean, Himpun (English Lecturers and Teachers Association (ELTA), 2025)
The aims of this research was to find out the improvement on students’ speaking ability after being taught by using Audio-Lingual method. This research applied quantitative research method with 60 students of SMA Anugerah Harapan Negeri Medan, 30 students as sample in the experimental group and 30 students in the control group. The data were collected trough speaking test. The students were asked to listened the short paragraph then asked the student repeated, imitated and memorized the text then the students were asked to record what the students listened. The data were collected in form of recording. The result showed that mean of the students ability using Audio-Lingual Method and without the treat mean were different. The data obtained from the score were the result of the experimental and control class. From the total score pre test of the experimental class (1.574) and the total score pre test of the control class (1.424) can be concluded that the achievement of both group was the same. After getting the treatment (Audio-Lingual Method), the total score post-test of the experimental (2.305) was higher than the total score post-test of the control class (1.654) which did not get the treatment. It can be said that the speaking ability of the students of Eleven grade SMA Harapan Negeri have increased Key Words : Audio-Lingual, Method, Speaking Ability